1990
DOI: 10.1139/g90-092
|View full text |Cite
|
Sign up to set email alerts
|

Genome elimination in diploid and triploid Rana esculenta males: cytological evidence from DNA flow cytometry

Abstract: Cytological aspects of hemiclonal (meroclonal) inheritance in diploid and triploid males of the hybridogenetic frog Rana esculenta (Rana ridibunda x Rana lessonae) have been studied by DNA flow cytometry. The fact that the R. ridibunda genome contains 16% more DNA than the R. lessonae genome provides the ability to discern cells containing genomes of any species from the water-frog complex under study. Data are presented showing that elimination of the R. ridibunda genome occurs in hybridogenetic males from ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 17 publications
5
76
0
1
Order By: Relevance
“…Our GISH data applied to the whole P. esculentus genome correspond well with former studies on DNA content in erythrocytes of water frogs. Flow [Borkin et al, 1987;Vinogradov et al, 1990] and image [Ogielska et al, 2004] DNA cytometry showed that the P. ridibundus genome contains 10-16% more DNA than that of P. lessonae . Bi and Bogart [2006] reported stronger hybridization signals of GISH probes in the pericentromeric regions of all chromosomes in the Ambystoma hybrid complex.…”
Section: Discussionmentioning
confidence: 99%
“…Our GISH data applied to the whole P. esculentus genome correspond well with former studies on DNA content in erythrocytes of water frogs. Flow [Borkin et al, 1987;Vinogradov et al, 1990] and image [Ogielska et al, 2004] DNA cytometry showed that the P. ridibundus genome contains 10-16% more DNA than that of P. lessonae . Bi and Bogart [2006] reported stronger hybridization signals of GISH probes in the pericentromeric regions of all chromosomes in the Ambystoma hybrid complex.…”
Section: Discussionmentioning
confidence: 99%
“…esculenta but not in the other three species. VINOGRADOV et al (1990) based their studies on the finding that the -R. ridibunda genome contained 16 % more DNA than the R. lessonae genome. Perhaps this excess DNA is located mostly in the first and the largest chromosomal pair.…”
Section: Cytogenetic Analysismentioning
confidence: 99%
“…As we have said, in hybridogenetic reproduction one of the parental genomes is not transmitted to the next generation and is discarded before premeiotic synthesis of DNA (VINOGRADOV et al 1988;VINOGRADOV et al 1990). However, studies of the pattern of inheritance in diploid Rana kl.…”
Section: Introductionmentioning
confidence: 99%
“…Similar processes occur in hybridogenetic vertebrates: in diploid hybridogenesis, one genome is transmitted clonally through the hybrid lineage, while the other is transmitted sexually by one of its parental species [6]. In meiotic hybridogenesis, both of the hybridizing genomes can be transmitted sexually, through crosses between diploid and triploid hybrids of different genomic compositions (figure 1; [14,16]). …”
Section: Introductionmentioning
confidence: 99%